2013
DOI: 10.1371/journal.pone.0057516
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Dependent Alterations in Regional Homogeneity of Baseline Brain Activity in Schizophrenia

Abstract: Low frequency oscillations are essential in cognitive function impairment in schizophrenia. While functional connectivity can reveal the synchronization between distant brain regions, the regional abnormalities in task-independent baseline brain activity are less clear, especially in specific frequency bands. Here, we used a regional homogeneity (ReHo) method combined with resting-state functional magnetic resonance imaging to investigate low frequency spontaneous neural activity in the three different frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 71 publications
7
51
1
Order By: Relevance
“…This was consistent with the results of previous studies [4,5,20]. More detailed correlations between cognitive impairment and regional spontaneous activity of aMCI patients in the resting-state fMRI studies should be further investigated.…”
Section: Effects Of Regional Brain Atrophysupporting
confidence: 92%
See 2 more Smart Citations
“…This was consistent with the results of previous studies [4,5,20]. More detailed correlations between cognitive impairment and regional spontaneous activity of aMCI patients in the resting-state fMRI studies should be further investigated.…”
Section: Effects Of Regional Brain Atrophysupporting
confidence: 92%
“…To further investigate the effects of regional brain atrophy on ReHo, we calculated the regional atrophy index within each region showing significant between-group differences on ReHo [20]. We performed the voxel-based morphometry (VBM) analysis on the T1-weighted images using the toolbox in SPM8 (VBM8 http://dbm.neuro.uni-jena.de/vbm/).…”
Section: Regional Atrophy Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…(We adopted the recommended neighborhood size of 26; In this way, ReHo can map the level of regional activity across the whole brain of an individual (Kiviniemi, 2008). This method has been successfully applied in studies of several psychiatric illnesses, such as schizophrenia (Yu et al 2013), depression (Yao et al 2009), attention deficit hyperactivity disorder (Cheng et al 2012) and Alzheimer's disease (AD; He et al 2007). The findings of these ReHo studies were essentially compatible with other R-fMRI studies (Liu et al 2008;Tomasi & Volkow, 2012;Zhao et al 2012;Tao et al 2013) of these illnesses, most of which used the functional connectivity method and examined the brain changes at the network level.…”
Section: Reho Computationmentioning
confidence: 99%
“…Schizophrenia patients showed smaller clusters of greater amplitude of low-frequency fluctuations in the caudate, including the frontal, temporal/insular regions, putamen, and hippocampus, in an fMRI study in a resting state [88]. A regional homogeneity (ReHo) method combined with resting-state fMRI showed that ReHo abnormalities in schizophrenia were frequency-dependent in the inferior occipital gyrus and caudate body, suggesting abnormality in brain oscillation [89]. These findings suggested that dysfunction in the caudate nucleus is involved in cortico-striatal functional connectivity.…”
Section: Caudate Regions In the Right Hemispherementioning
confidence: 99%